Commentary on Matthew - Jerome, Saint, -419 or 420 (Fathers of the church, 2008)
"St. Jerome (347-420) has been considered the pre-eminent scriptural commentator among the Latin Church Fathers. His Commentary on Matthew, written in 398 and profoundly influential in the West, appears here for the first time in English translation." "Jerome covers the entire text of Matthew's gospel by means of brief explanatory comments that clarify the text literally and historically. Although he himself resided in Palestine for forty years, Jerome often relies on Origen and Josephus for local information and traditions. His stated aim is to offer a streamlined and concise exegesis that avoids excessive spiritual interpretation." "In this commentary, Jerome calls attention to the activity of the Trinity as a principal unifying theme of the Gospel of Matthew. He also stresses that exertions are necessary for the Christian to attain eternal salvation; that free will is a reality; that human beings cooperate with divine grace; and that it is possible to obtain merit during the earthly life."--Jacket